Duchowość w czasach popkultury: Metafizyczne eksperymenty w filmowej fantastyce - Drozdowicz, Jarema (Przegla̜d religioznawczy, 2013)
The main purpose of the present considerations would be to capture the phenomenon of materialisation of spiritual reality, which can be studied on the basis of selected contemporary movies. The analysis would involve: Star Wars Episode I - The Phantom Menace, The Matrix, The Lost Room, and Avatar. This problem is all the more interesting as the authors of these productions attempt - often unwittingly - to provide interpretations of classical metaphysical categories. The issue of mutual interrelationships between the corporal and the spiritual has obviously been within the scope of metaphysical interest for centuries. The analysed phenomenon is also interesting due to the fact that these movies belong to the flagship products of contemporary popular culture. Consequently, their cinematic distribution assumes a universal and global character, which facilitates their impact on entire societies.